Acceptance and commitment therapy: the new wave of cognitive behavior therapy - Wahyu Nanda Eka Saputra; Santi Widiasari (Indonesian Counselor Association, 2016)
Cognitive behavior therapy (CBT) is one of the major counseling theories today. However, reliability of this theory has received criticism from other theories, which claim to cognitive interventions do not provide added value on behavioral interventions. The theory criticized and showed dissatisfaction with the practice of CBT is the theory of Acceptance and Commitment Therapy (ACT). Furthermore, ACT is known to a new generation of CBT.ACT is one of the new counseling approach that can be applied to school counselors to deal with the issues of students in the school.